Effect of High-Intensity Interval Training and unification training on Aerobic Capacity and Muscle Strength in Intermediate Distance Runners- a systematic review - Ricky Susiono; FX Sugiyanto; Ria Lumintuarso; Tomoliyus Tomoliyus (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction and Objectives: Aerobic capacity and muscular strength are two important physical components that influence the performance of middle-distance runners. High-intensity interval Training (HIIT) and unification training have been recognized as effective methods for improving these parameters. However, scientific evidence comprehensively examining the effects of these two methods on middle-distance runners is limited. Therefore, this study aimed to systematically evaluate the impact of HIIT and unification training on the aerobic capacity and muscle strength of middle-distance runners.